Kajian Teoritis Pembiayaan Mudharabah Dan Murabahah Pada Perbankan Syariah - Erliyanti Erliyanti (LPPM Universitas Labuhanbatu, 2023)
Islamic banking operates on the principle of profit sharing. The development of Islamic banking in Indonesia cannot be run purely sharia, because Islamic banks run a system by imposing a system of profit sharing and risk. This paper aims to review and examine the practice of mudharabah and murabaha financing in Islamic banking. The methodology used is field research conducted by exploring data sourced from locations or research fields relating to the types of products that exist in Islamic banking, among the products studied are murabahah and mudharabah financing products and the mechanism of how they work. Besides that, this research also uses literature research using literature, either in the form of books, notes, or reports on the results of previous research. The results of this study indicate that murabahah financing is superior to mudharabah financing. Because murabahah financing is short-term financing for the purchase of goods, even though the customer does not have the money to pay for it, he can get the goods according to his wishes after going through the specified process stages.